Harga Diri dan Schadenfreude pada Karyawan - Ubino, Sity Nurhaliza; Rahmatulloh, Ainurizan Ridho (Merpsy Journal, 2023)
Employees are required to build harmonious relationships between workers in order to create work productivity. However, in reality conflicts between employees still occur frequently. This study aims to determine the relationship between self-esteem and Schadenfreude in empoyees. The hypothesis in this study is that there is a relationship between self-esteem and Schadenfreude. The subjects in this study were employees who worked in an agency or company with an age range of 18 years and over and working for more than 1 year. Data collection techniques will use the self-esteem scale and Schadenfreude scale. The data were analyzed using pearson's correlation product moment in the SPSS version 26 software program. Based on the results of the analysis, the correlation coefficient values was -0.624 and p=0.000. (p≤0.050). These results indicate a significant negative relationship to self-esteem and Schadenfreude. The coefficient of determination R2 is 0.390, which means that self-esteem has a relationship of 39% to Schadenfreude while the remaining 61% is influenced by other factors.